AHP 28: Review: Transforming Nomadic Resource Management and Livelihood Strategies - Daniel, Winkler (Asian Highlands Perspectives, 2018)
In late 2012, Andreas Gruschke published a densely packed, 450 page book based on his PhD dissertation, on the transformation of nomad livelihoods in Yushu [Yul shul] Tibetan Autonomous Prefecture (TAP).1 It is volume fifteen of the series of 'Nomaden und Sesshafte (Nomads and Settled People)' published by the Sonderforschungsbereich Differenz und Integration – Wechselwirkung zwischen nomadischen und sesshaften Lebensformen in Zivilsationen der Alten Welt (Special Collaborative Research Center, Difference and Integration: Interdependency Between Nomadic and Settled Life-forms in Old World Civilizations). The background information, rich data, dozens of detailed interviews with former and current nomads, and the findings in this publication are the result of eight years of study, including a total of sixteen months of fieldwork by Gruschke in Tibetan areas of Qinghai Province and neighboring Tibetan areas. This book contains case studies that have never been previously presented, and introduces these highland communities' current situation in a clear, detailed, and discriminating light that is rich in data.